The Effectiveness Of Homophone Gamestowards Student’s Pronunciation At MTsN Kepulauan Selayar - Isra Yulianti; Hasnani Hasnani; Suharti Siradjuddin (Publikasi Indonesia, 2022)
Speaking English with precise and accurate pronunciation is an ability that is highly desired by all students. However, in reality there are still many students who find it difficult to apply it in everyday life both at school and at home. Therefore, this study aims to find out how students pronounce before and after using homophone games and how effective the use of homophone games on student pronunciation in class VII B MTsN Kepulauan Selayar. This type of research is pre-experimental with one group pre-test and post-test, carried out in four stages, namely pre-test, treatment, post-test, and observation. The subjects of this study were students of class VII B MTsN Kepulauan Selayar totaling 16 people where there were 10 male students and 6 female students. Data collection techniques used are tests, and documentation. The results showed that through the homophone game the pronunciation of students in grade VII B MTsN Kepulauan Selayar was more effective. It can be seen from the students' pre-test and post-test scores increased, from 48.81 to 59.62, with a score range of 10.81. Meanwhile, the standard deviation for the pre-test is 0.3725 and the post-test is 0.4045, with a value range of 0.032. Where the value of the t-test is greater than the t-table, namely 787,108 1,75305. So, based on the results of the data analysis above, the researcher can conclude that the use of homophone games for class VII B students of MTsN Kepulauan Selayar is more effective.